Pseudouridylate Synthetase of Escherichia coli: Correlation of Its Activity with Utilization of Pseudouridine for Growth - Breitman, T. R. (1970)
A direct correlation exists between the pseudouridylate synthetase activity and the ability of pyrimidine auxotrophs of Escherichia coli to grow on pseudouridine.